Beyond post-traumatic stress : homefront struggles with the wars on terror - Hautzinger, Sarah J., 1963- (Left Coast Press, 2014)
"When soldiers at Fort Carson were charged with a series of 14 murders, PTSD and other "invisible wounds of war" were thrown into the national spotlight. With these events as their starting point, Jean Scandlyn and Sarah Hautzinger argue for a new approach to combat stress and trauma, seeing them not just as individual medical pathologies but as fundamentally collective cultural phenomena. Their deep ethnographic research, including unusual access to affected soldiers at Fort Carson, also engaged an extended labyrinth of friends, family, communities, military culture, social services, bureaucracies, the media, and many other layers of society. Through this profound and moving book, they insist that invisible combat injuries are a social challenge demanding collective reconciliation with the post-9/11 wars"--